alguém me ajuda... e a (m+1....
Anexos:
![](https://pt-static.z-dn.net/files/d36/0b33fd29fb5e36e9cdec2034206503b9.png)
Soluções para a tarefa
Respondido por
1
(y - 7)(y + 7) = y² - 7² = y² - 49
(1 - 5x)(1 + 5x) = 1² - (5x)² = 1 - 25x²
(m + 1/2)(m - 1/2) = m² - (1/2)² = m² - 1/4
(x³ - 2)(x³ + 2) = (x³)² - 2² = x^6 - 4
(1 - 5x)(1 + 5x) = 1² - (5x)² = 1 - 25x²
(m + 1/2)(m - 1/2) = m² - (1/2)² = m² - 1/4
(x³ - 2)(x³ + 2) = (x³)² - 2² = x^6 - 4
Perguntas interessantes
Matemática,
11 meses atrás
Ed. Física,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás